Analysis of Operation Purified Pater System in the Pharmaceutical Field of PT. Nulab Pharmaceutical Indonesia - Noviawati, Lilis; Irwanto, Irwanto (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2021)
Health is an indicator of the level of human welfare so that it becomes a priority in the national development of a nation. This is related to efforts to improve the quality of the nation's resources. With quality human resources, it will further increase the nation's competitiveness in the current era of global competition. The main form of the application of technology is as a driving force for the advancement of science and technology and the times, in making work more efficient. Currently, many factories in the pharmaceutical industry have used a purified water system, for example a water management system in the manufacture of drugs. The objectives of this study are (1) to determine the Purified Water System process in the pharmaceutical sector. (2) knowing the performance system in the Purified Water System process in the pharmaceutical sector, (3) analyzing the results of the Regeneration of the Purified Water System in the pharmaceutical sector. The research method used is qualitative research with a descriptive approach. The data collection techniques include observation, interviews, literature study and documentation. The data analysis technique used an interactive method developed by Miles & Huberman. The results of this study indicate that the working mechanism of the Purified Water System is a water treatment system that can remove various contaminants (ions, organic matter, particles, microbes and gases) in the water to be used for production. Water (raw water) water treatment can be obtained from PDAM water (city water), Shallow well (shallow well) with a depth of 10-20 m, or from deep wells (deep wells) with a depth of 80-150 m. Variations in the quality of raw water supplies that meet the requirements are determined from the water quality target to be produced. Likewise, water quality determines the equipment needed for water treatment. Keywords: Purified water system, pharmacy, analysis, operationDOI: http://dx.doi.org/10.23960/jpvti.v3.i1.202107